Associação entre medidas morfométricas e ultrassonográficas na estimação da produção de leite de caprinos leiteiros - Galvão, Maria Andreia Alves (2016)
The aim of this study was to evaluate the associations between morphometric and ultra-sound measurements and the milk yield of goats, to identify of animals with better production efficiency. Thirty-six does 18 from Saanen breed and 18 from Anglo-Nubian breed. The measured morphological traits were: udder depth (UD), udder width (UW), distance from the teat to the ground (DCG), distance between teat (DBT), length (LT) and diameter of the teat (DT). The ultra-sonographic traits analyzed were: teat canal length (TCL), teat diameter (TD), wall thickness of the teat (WTC), cistern area of the teat (CAT) and cistern area of the gland (CAG). Daily milk yield (MY) was estimated as the average of the last test-day milk yield. In both breeds, there was no significant associations between morphometric/ultra-sonographic traits and the milk yield. Only CAG was correlated with MY (r = 0.57; P <0.05), in the Anglo-Nubian breed, and UW (r = 0.48; P <0.05) in Saanen breed. In the Anglo-Nubian breed, longer and larger diam-eter teat tend to increase the proximity of the udder to the ground, while this is more evident in deeper udders in Saanen breed. In both breeds, longer teat also feature larger diameter. The canonical correlation analysis showed that the sets of morphometric and ultra-sonographic traits present high association (r = 0.9455). The first canonical pair explained 93.21% of the total variation contained in the data set. DC, LC and DCG traits were the most associated with the set of ultra-sonographic canonical variables, while DC and CAT were most associated with the set of morphological canonical varia-bles. The morphological traits to be measured to aid the production of goat milk depend on the breed into consideration, which may be a function of up selective history of this breed. The measurements carried out on the teat have higher correspondence with those performed with ultrasound than those measured in the udder. Length and diameter of the teat and its ground clearance are the most should be considered as an aid to selection for milk production in goats.